2010
DOI: 10.3208/sandf.50.27
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on the Behavior of Unsaturated Compacted Silt Under Triaxial Compression

Abstract: Most of the experimental investigations conducted on unsaturated soil have been performed under a constant air pressure. Changes in air pressure during deformation are in some cases important in practice. For example, in order to explain the stability problems of embankments during earthquakes and seepage ‰ow, and grounds containing gas associated with the dissociation of methane hydrates, it is necessary to consider the interaction between the soil and the pore ‰uids. In the present study, we carried out full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…The eŠects of the initial suction, the conˆning pressure, and the degree of compaction under fully undrained conditions, namely, constant water and constant air shearing tests, as well as under drained conditions for both air and water, were studied. For the stress variables of the unsaturated soil, the skeleton stress was used to describe the experimental results and was deˆned as the diŠerence between the total stress tensor and the average pore pressure of water and gas (Oka et al, 2010). From the monotonic and cyclic test results, we found that the stress-strain behavior of unsaturated sandy soil strongly depends on the initial suction, especially under fully undrained conditions, due to the diŠerence in pore pressures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The eŠects of the initial suction, the conˆning pressure, and the degree of compaction under fully undrained conditions, namely, constant water and constant air shearing tests, as well as under drained conditions for both air and water, were studied. For the stress variables of the unsaturated soil, the skeleton stress was used to describe the experimental results and was deˆned as the diŠerence between the total stress tensor and the average pore pressure of water and gas (Oka et al, 2010). From the monotonic and cyclic test results, we found that the stress-strain behavior of unsaturated sandy soil strongly depends on the initial suction, especially under fully undrained conditions, due to the diŠerence in pore pressures.…”
Section: Introductionmentioning
confidence: 99%
“…However, many of their studies were conducted under drained conditions for both the pore air and the pore water, i.e., constant suction conditions, or undrained conditions for only the pore water and drained conditions for the pore air, due to the di‹culty of measuring or controlling the air pressure. Recently, Nishimatsu et al (2004), Kodaka et al (2006), and Oka et al (2010) conducted triaxial tests under fully undrained conditions, namely, constant water and constant air shearing tests, and discussed the importance of air pressure on the mechanical behavior of unsaturated silty soil. In practice, drained conditions for water and air cannot always be attained; for example, the increase in air pressure in a river embankment during the seepage process was observed when air was trapped in parts of an embankment during heavy rains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, skeleton stress (Jommi, 2000;Gallipoli et al, 2003) is used for the stress variable in the constitutive relation for the soil skeleton (Oka et al, 2006(Oka et al, , 2008b(Oka et al, , 2010Kimoto et al, 2007). The total stress tensor is assumed to be composed of three partial stresses for each phase.…”
Section: Skeleton Stressmentioning
confidence: 99%
“…In the MPM, constitutive equations can be easily applied because history-dependent variables, such as plastic strain and strain-hardening parameters, are carried by each material point. As the stress variable of the constitutive model, skeleton stress (Jommi, 2000;Gallipoli et al, 2003) is used to describe the mechanical behavior of unsaturated soils (Oka et al, 2006(Oka et al, , 2008b(Oka et al, , 2010Kimoto et al, 2007). For the full description of the behavior of unsaturated soil, it is necessary to incorporate the suction in the constitutive model.…”
Section: Introductionmentioning
confidence: 99%